Pengaruh Penyuluhan Dalam Meningkatkan Pengetahuan Nutrisi Bagi Ibu Hamil Terhadap Pola Konsumsi Pangan Sebagai Upaya Pencegahan Stunting - Fadhilah, Tri Marta; Khofipah, Hepi; Heriyanta, Yanti; Cahya, Indi; Febrianti, Eriana (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Nutritional status in pregnant women is an important indicator in describing the health situation in pregnant women. Measurement of nutritional status in pregnant women can be done, one of which is by measuring Upper Arm Circumference (LiLA). If LiLA < 23.5 cm, pregnant women are at risk of Chronic Energy Deficiency (SEZ). The nutritional status of pregnant women has a significant influence on the incidence of anemia in pregnant women, SEZ deficiency and low birth weight (BBLR). This study aims to determine the influence of providing nutrition education and the influence between knowledge and the diet of pregnant women at the Duren Jaya Bekasi Health Center. This type of research is quantitative using a research design one group pre test-post test desgin. Data collection at Duren Jaya Health Center with a sample of 25 respondents selected by consecutive sampling. The instrument of this study is a questionnaire. Data were analyzed using paired t-test for nutritional knowledge and chi square test for influence of knowledge and diet. The results of the study were that there was a relationship between before counseling and after counseling with results of 0.041 < 0.05 (p-value). There was no relationship between knowledge of pregnant women and maternal dietary behavior during pregnancy 0.25 < 0.05 (p-value).